Optimization of Turbine Blade Pitch Angle of a Home-built Wind Turbine for Maximum Power Output - Mugo, Sammy; H. Masinde, Barasa; T. Cherop, Peter (UIR PRESS, 2024)
Wind energy greatly reduces the world’s dependence on fossil fuels (oil and natural gas), and is environmentally friendly. One of the most cost-effective alternatives of energy sources is wind power. This study used a horizontal axis wind turbine to investigate the optimal blade pitch angle that can give maximum electrical output. A proportional integral derivative pitch controller was used to establish blade pitch angles. Wind speeds of 3, 4, 5 and 6 m/s were run at every pitch angle respectively, and a maximum electrical power output was 1124.7W at a blade pitch angle of 16.80 when a wind speed of 6 m/s was used. Every wind speed was run for 100 seconds. A simulation, using Visual Basic 6 software, was done at the respective blade pitch angles, and a wind speed of 6 m/s. The electricity produced was recorded. The simulated electrical power produced yielded a relationship that predicted the electrical power output with a coefficient of determination (R2) of 0.9752; this shows a very close agreement with actual electric output values.